2007
DOI: 10.1007/s00148-006-0124-5
|View full text |Cite
|
Sign up to set email alerts
|

Sibling size and investment in children’s education: an asian instrument

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
142
0
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 166 publications
(152 citation statements)
references
References 17 publications
5
142
0
2
Order By: Relevance
“…So for instance for female first-borns, we construct three analysis samples: those in families with n≥2 (instrument=female at 2 nd birth; 'ff'); those in families 6 Sex composition was first used as an instrument for family size by Angrist and Evans (1998) and has since been applied by others such as Angrist et al (2010) and Conley and Glauber (2006). These studies use same-sex births as the instrument, whether all-male or all-female; Lee (2008) on the other hand uses all-female births. Another commonly used instrument is twin births.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…So for instance for female first-borns, we construct three analysis samples: those in families with n≥2 (instrument=female at 2 nd birth; 'ff'); those in families 6 Sex composition was first used as an instrument for family size by Angrist and Evans (1998) and has since been applied by others such as Angrist et al (2010) and Conley and Glauber (2006). These studies use same-sex births as the instrument, whether all-male or all-female; Lee (2008) on the other hand uses all-female births. Another commonly used instrument is twin births.…”
Section: Methodsmentioning
confidence: 99%
“…In both cases, the direction of the resulting bias of the IV estimate is positive: if postnatal son preferences exist (and affect education decisions), then a sister is more beneficial for girls' schooling than a brother; if scale economies are important, savings may be higher in all-female households (relative to mixed gender households), which is also beneficial for schooling. 29 Concerning son preferences, Lee (2008) points out that the instrument concerns prenatal and not postnatal son preferences, in other words that parents prefer to have sons rather than daughters ex-ante, and not that parents treat sons more favourably than daughters ex-post. 28 Exceptions include Rosenzweig and Wolpin (2000) and Rosenzweig and Zhang (2009), who provide direct evidence on the likely validity of same-sex and twin instruments respectively.…”
Section: Evidence On Instrument Validitymentioning
confidence: 99%
See 1 more Smart Citation
“…We use, as an instrument, a binary variable that is equal to one if the first-born child is a girl, and to zero otherwise. The effects of the first-born's gender have been analysed in various papers (Rosenzweig and Wolpin, 2000), in Asia (Chowdhury and Bairagi, 1990;Clark, 2000;Dreze and Murthi, 2001;Lee, 2008;Li and Wu, 2011;Milazzo, 2014b), and more recently, in Sub-Saharan Africa (Milazzo, 2014a). In Nepal, as in other countries, there is a strong preference for boys.…”
Section: Empirical Strategymentioning
confidence: 99%
“…Kawaguchi and Miyazaki (2009) used data from Japan to test this argument and found that men raised by full-time working mothers are less likely to support traditional gender roles and are also less likely to believe in the negative effect of a mother working on her children's development. 3 It is widely acknowledged that family structure, such as birth order and the number of siblings, leads to different economic outcomes; for example, accumulation of human capital (e.g., Berman and Taubman, 1986;Kessler, 1991;Hanushek 1992;Oettinger 2000;Black et al 2005;Kantrevic and Mechoulan, 2006;Lee 2008;Dayiogru et al 2009;Dammert, 2010;Cho 2011;Buckles and Munnich 2012), participation in the labor market (Edmonds, 2006), child mortality (Makepeace and Pal 2008;Chamarbagwala, 2011), and inequality (Mazumder 2008). This might be partly because of large birth-order differences in the amount of quality lime that children spend with their parents (Price 2008).…”
Section: Introductionmentioning
confidence: 99%